Explorando o potencial da criação de vídeos por alunos como estratégia de aprendizagem em física no Ensino Médio - Visoli, Cleodinei (2019)
The process of teaching and learning Physics in high school has proved to be a challenge to teachers and students. There is a lack of use of strategies that emphasize the use of technological resources present in the student's daily life, with the content delivered in the classroom. The present work aimed at analyzing the employability of the elaboration and development of videos made by the students in the contribution to the for mation of concepts that relate to a significant learning to the teaching of Physics. In the light of this, a didactic sequence was developed for the production of videos by the students, describing the construction of a mechanical apparatus and the physica l phenomena present in it, in order to answer the following question: how does the process of video construction developed by the students, reporting the elaboration and construction of mechanical devices, linked to Physics, creates conditions for meaningful learning? To answer this questioning, the study is characterized as a qualitative approach, using as indicators the practical activity developed, the records in the teacher's field diary, the answers presented to the questions, the discussions carried out by the students and the observed reports. For that, an educational product was elaborated: Production of videos as strategy of teaching Physics in High School. Which, presents a didactic sequence organized in 11 meetings, and applied in a class of the t hird year of high school. The analysis of the data collected allowed us to point out the feasibility of the methodological proposal, as a complementary tool to Physics teaching. It was noticed a great commitment of the students, evidenced by the expressive participation of them in the meetings, in the enthusiasm as to the making of the practical activities and in the resourcefulness of the realized presentations. Factors that indicate that the activity developed meets the necessary requirements for the development of meaningful learning. The methodology used for its application is an interesting alternative to the teaching of Physics in schools, approaching resources present in the daily life of the student with its use as acquisition of knowledge. The educational product accompanying the study refers to the elaborate didactic sequence and is made available in the form of teacher support material on the program website and the EduCapes Portal <http://educapes.capes.gov.br/handle/capes/432306>.